QUALITY BY DESIGN APPROACH FOR RP-HPLC METHOD DEVELOPMENT AND VALIDATION OF CABOTEGRAVIR FROM BULK DRUG AND DOSAGE FORM (International Journal of Pharmaceutical Sciences and Drug Research, 2025)
A robust reversed-phase chromatographic method was developed for the analysis of Cabotegravir in pure form and tablets. Using Design Expert software version 8, the technique was optimized through a central composite design with an emphasis on peak symmetry, theoretical plates, and retention time. A 50:50 ratio of mobile phase consisting of acetonitrile and phosphate buffer (pH 4) at a flow rate of 1 mL/min, and a column oven temperature was 27.5°C were ideal parameters. Detection was performed at 256nm using BDS HypersilTM C18 column and a PDA detector, with a run time of 10 minutes. The method’s specificity, linearity, accuracy, robustness, precision was all verified. Linearity was noted in the range of 10-50µg/mL, with correlation coefficient of 0.999. The % RSD for intraday and interday precision was 1.67% and 1.97%, respectively. Accuracy, as % recovery, was 100.70% at 80%, 98.91% at 100%, and 101.83% at 120% concentration levels. 1.8µg/mL was the limit of detection (LOD), and 5.4µg/mL was limit of quantification (LOQ). All validation parameters were within the acceptable limits of the ICH Q2(R1) guideline. Forced degradation studies were conducted under acidic, alkaline, oxidative, photolytic, and thermal stress conditions. The drug demonstrated greater degradation in alkaline and oxidative conditions.